A methodology for multiple domain feature mapping - Lim, Seng San (2009)
Feature technology provides a high level representation that is capable of capturing more engineering information than conventional solid modeling techniques, such as boundary representation (Brep) and constructive solid geometry (CSG), which are commonly available in many computer-aided design (CAD) systems. The information tends to be domain specific and application dependent. It is therefore only relevant to the reasoning requirements of a particular domain. In order to bridge the gap between the different application-dependent feature-based models, an effective feature mapping methodology is needed.